2018
DOI: 10.1177/0284185118784981
|View full text |Cite
|
Sign up to set email alerts
|

Validation and reproducibility of cardiovascular 4D-flow MRI from two vendors using 2 × 2 parallel imaging acceleration in pulsatile flow phantom and in vivo with and without respiratory gating

Abstract: Background 4D-flow magnetic resonance imaging (MRI) is increasingly used. Purpose To validate 4D-flow sequences in phantom and in vivo, comparing volume flow and kinetic energy (KE) head-to-head, with and without respiratory gating. Material and Methods Achieva dStream (Philips Healthcare) and MAGNETOM Aera (Siemens Healthcare) 1.5-T scanners were used. Phantom validation measured pulsatile, three-dimensional flow with 4D-flow MRI and laser particle imaging velocimetry (PIV) as reference standard. Ten healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 27 publications
(40 reference statements)
3
42
0
Order By: Relevance
“…The main strength of this study was its use of an in vitro aortic phantom connected to a closed-circuit-flow system that simulated human aortic velocity and pressure [24][25][26][27][28][29]. Phantom studies that simulate human circulation enable repeated CT scans without the risk of radiation damage and iodine exposure in human subjects and can provide thousands of datasets by manipulating multiple variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main strength of this study was its use of an in vitro aortic phantom connected to a closed-circuit-flow system that simulated human aortic velocity and pressure [24][25][26][27][28][29]. Phantom studies that simulate human circulation enable repeated CT scans without the risk of radiation damage and iodine exposure in human subjects and can provide thousands of datasets by manipulating multiple variables.…”
Section: Discussionmentioning
confidence: 99%
“…The conditions of pump and phantom devices were carefully manipulated while monitoring velocity and pressure to simulate human circulation, since the reliability of this feasibility study depends on the degree of agreement between the in vitro phantom simulation and actual human circulation. Although fine adjustments in the pump and phantom devices were made to produce bolus geometry mimicking human circulation [24][25][26][27][28][29], the differences might had affected the experimental results. Despite the precisions revealed from the repeated scanning or the trends found in this phantom study, particular cautions need to be taken in the context of clinical interpretation, and this study's results need to be confirmed in a successive clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons for this residual error. While the realistic anatomical model is a strength of this work, it also 36 432 333 334 437 743 (9) Speed (20) 85 (17) 95 (14) 110 (18) 140 (1.8) 86 (17) 98 (28) 130 (31) 180 (24) 240 (36) WSS Corr. Coeff.…”
Section: Limitationsmentioning
confidence: 99%
“…Three dimensional cine phase‐contrast MRI (4D‐flow MRI) is used as a regular research modality in cardiac MRI and is becoming more widely adopted as a utility for clinical assessment . Obstacles to its full adoption in routine clinical practice include difficulties in postprocessing and variability among studies investigating its reliability and accuracy of measurements . Vascular flow‐volume measurements are an integral component of cardiovascular MR examinations.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Obstacles to its full adoption in routine clinical practice include difficulties in postprocessing and variability among studies investigating its reliability and accuracy of measurements. 3,4 Vascular flow-volume measurements are an integral component of cardiovascular MR examinations. The 4D-flow MRI enables retrospective flow-volume measurements at any vessel location following the conclusion of the imaging study.…”
Section: Introductionmentioning
confidence: 99%